2016
DOI: 10.1242/jeb.153320
|View full text |Cite
|
Sign up to set email alerts
|

Predator stress-induced immunosuppression: trade-off, immune redistribution or immune reconfiguration?

Abstract: Although predator exposure increases the risk of wound infections, it typically induces immunosuppression. A number of non-mutually exclusive hypotheses have been put forward to explain this immunosuppression, including: trade-offs between the immune system and other systems required for anti-predator behaviour, redistribution of immune resources towards mechanisms needed to defend against wound infections, and reconfiguration of the immune system to optimize defence under the physiological state of fight-orfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 65 publications
(85 reference statements)
1
27
0
1
Order By: Relevance
“…Prolonged predation risk is often interpreted as a factor responsible for chronic stress and reduction in prey fitness, including impairment of defence abilities 14 as well as direct mortality 15,16 . On the other hand, prolonged exposure to predator signals has been demonstrated to induce reconfiguration of physiological processes necessary to compensate the costs of the defence reaction [17][18][19] . Moreover, some studies demonstrated that individuals pre-exposed to predation cues were better prepared to predator pressure than non-stressed ones 20,21 .…”
mentioning
confidence: 99%
“…Prolonged predation risk is often interpreted as a factor responsible for chronic stress and reduction in prey fitness, including impairment of defence abilities 14 as well as direct mortality 15,16 . On the other hand, prolonged exposure to predator signals has been demonstrated to induce reconfiguration of physiological processes necessary to compensate the costs of the defence reaction [17][18][19] . Moreover, some studies demonstrated that individuals pre-exposed to predation cues were better prepared to predator pressure than non-stressed ones 20,21 .…”
mentioning
confidence: 99%
“…Mangahas et al . ); immunosuppression in response to chronic predation risk appears to be a common, but not universal, response that arises from trade‐offs and from a physiological network of stress and immune responses (Adamo et al ., ; Adamo, ). By contrast, the present study exposes larvae over a relatively limited time period (72 hours) making this an acute, rather than chronic exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Predator‐induced physiological plasticity can take many forms, depending on the interactions between stress responses and immune function (Adamo, ,b). Recent evidence has shown that exposure to predator cues can induce heightened immune responses by prey in some contexts (Duong and McCauley, ; Adamo et al ., ), possibly as a response to the increased risk of wounding by predators (Dhabhar, ). However, predator exposure can also be immunosuppressive (Adamo et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Одним из направлений исследований С.А. Адамо (Ada mo, 2012(Ada mo, , 2014(Ada mo, , 2017aAdamo et al, 2013Adamo et al, , 2017 является изучение стрессзависимой иммунной функции с использованием моделей насекомых. Показано, что у насекомых медиаторы стрессового ответа (т. е. гормоны стресса) меняют иммунный статус насекомого, в том числе частично перераспределяя молекулярные ресурсы в пользу двигательной активности, интенсификация которой необходима для борьбы или бегства.…”
Section: тест-системы и биоиспытанияunclassified